Biomaterials, Medical Devices, and Combination Products Biocompatibility Testing and Safety Assessment - Gad, Shayne Cox Gad-McDonald, Samantha (CRC Press, 2016)
This is a completely revised and much expanded version of the third edition of Safety evaluation in the development of medical devices combination products.